Maurice Blanchot: comparison as enlightenment - Pacheco, Keli (Lettres Françaises, 2013)
The essay “O infinito e o infinito” by the writer, philosopher and literary theorist Maurice Blanchot presents an exercise in comparative literature between Jorge Luis Borges and the poetry of Henry Michaux, produced when the latter submitted himself to scientific tests on the use of mescaline. Blanchot unites distinct universes, and from the contact with the differences of the Latin American writer and the French writer, enlightenment occurs. From the study of Borges’s short story, “Tlön, Uqbar, Orbis Tertius”, in Fictions, and of two poetic fragments from Miserable Miracle, we could visualize what Blanchot called “the reversal power of literature”.